Analysis of EEG characteristics of paroxysmal functional disorders associated with combat stress - Mykytenko Роман; Gryshchenkova Ольга; Ivanovska Оксана; Zolotoryov Павло; Hrynchuk Ірина; Komarovskyi Максим (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.